Cardiovascular-kidney-metabolic syndrome — a new concept of the association of risk factors and metabolic disorders within the cardiovascular and renal continuum. View on the issue - G. G. Arabidze; M. N. Mamedov (Российский кардиологический журнал, 2024)
In 2023, the American Heart Association for the first time formally defined cardiovascular-kidney-metabolic (CKM) syndrome as a systemic disease characterized by pathophysiological interactions between metabolic risk factors, chronic kidney disease (CKD), and cardiovascular system, leading to multiple organ dysfunction and a common adverse cardiovascular outcomes. Data are presented based on the pathophysiological mechanisms and clinical manifestations that made it possible to define this syndrome through the interaction between metabolic risk factors, CKD and the cardiovascular system, leading to multiple organ dysfunction and a high level of adverse cardiovascular outcomes. A classification of this syndrome into stages has been determined, for each of which approaches to the diagnosis and management of patients have been defined. CKM syndrome reflects the influence of multisystem pathophysiological relationships embedded in a multi-level socially and clinically determined community of manifestations, the fusion of which specifies clinical outcomes.